Automated design optimization of CMOS VLSI operational amplifiers - Mangaser, Ramon A. (1993)
This thesis proposes and implements an algorithm that eliminates the tedious design iteration of the circuit design phase of MOS op-amps. The proposed algorithm automatically computes for the required optimized design of the op-amp from the design specifications and the analytical model of the op-amp. It is a combination of two algorithms: namely, Simulated Annealing and Nelder and Mead's Simplex Algorithm. The combination offers certain advantages: first, it is independent of the initial choice for the solution which is a common fault of ordinary optimization algorithms and second, it is faster than pure Simulated Annealing which takes a long time (due to the large number of iterations needed) to arrive at an optimum solution.
Computer print-out.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Operational amplifiers; Linear integrated circuits; Mathematical optimization; Simulated annealing (Mathematics).